Práticas de ensino de leitura e escrita na rede pública de Fortaleza: letramentos em contexto digital? - Almeida, Larissa Naiara Souza de (2023)
This research aimed to analyze the practice of teaching reading and writing developed by teachers of the second year of Elementary School, from the planning, execution and evaluation of these activities involving the use of digital technologies already handled by the children. Therefore, we specifically aimed to: 1) describe the planning of these teachers in relation to reading and writing activities with the use of digital technologies; 2) describe the teachers' guidance regarding the use of digital technologies by children in reading and writing activities; 3) outline the assessment that teachers make about children's reading and writing productions involving the use of digital technologies. In the development of the theoretical framework, we worked with the Psychogenesis of Written Language (FERREIRO; TEBEROSKY, 1999), with the relationship between literacy and literacy (SOARES, 1998; 2011, MORTATTI, 2004, TFOUNI, 2006, KLEIMAN, 2005), with literacy digital (COSCARELLI; RIBEIRO, 2017; XAVIER, 2005), with planning (LIBÂNEO, 2013) and with evaluation (LUCKESI, 2014, HOFFMANN, 2005). The research was developed within a qualitative approach (MINAYO; DESLANDES; GOMES, 2016), being a case study with an ethnographic air (LARCHERT, 2017; ANDRÉ, 2009). Our subjects were two teachers of the second year of Elementary School, from public schools in Fortaleza. The instruments chosen for the data construction process were the following, participant observation (MINAYO; DESLANDES; GOMES; 2016) and simple self-confrontation and cross selfconfrontation (FAÏTA, 1989). From the results obtained, we infer that the planning carried out by the teachers in very little contemplated the development and expansion of digital literacy, as it was characterized by excessive bureaucratic demands. Thus, there was a fragile autonomy on the part of the teachers due to demands for the results of external evaluations, more specifically the Spaece-Alfa. About the mediation of the teachers in relation to the use of the computer by the children, we could verify that there was only one change of support for the activities involving reading and writing, that is, from the textbook to the computer screen. Therefore, the proposed reading and writing activities basically emphasized aspects related to the descriptors charged in external assessments, leaving little room for the acquisition of knowledge inherent to digital literacy. Regarding the evaluation, this process was also strongly influenced by SpaeceAlfa, thus, the teachers' evaluation in relation to digital literacy was based on the demonstration of autonomy, interest and alphabetic literacy that the children appeared to have during the resolution of the activities of the Light of Knowledge.